2021
DOI: 10.3390/mi12010044
|View full text |Cite
|
Sign up to set email alerts
|

Surface Wettability and Electrical Resistance Analysis of Droplets on Indium-Tin-Oxide Glass Fabricated Using an Ultraviolet Laser System

Abstract: Indium tin oxide (ITO) is widely used as a substrate for fabricating chips because of its optical transparency, favorable chemical stability, and high electrical conductivity. However, the wettability of ITO surface is neutral (the contact angle was approximately 90°) or hydrophilic. For reagent transporting and manipulation in biochip application, the surface wettability of ITO-based chips was modified to the hydrophobic or nearly hydrophobic surface to enable their use with droplets. Due to the above demand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…38 The Q Y values of the graphene and graphene-CNC lms were 13.9 ± 2.7°and 64.0 ± 1.7°(n = 3, P = 0.0001), respectively, showing that graphene lms are more hydrophilic than graphene-CNC lms. The Q Y value of ITO was found to be 96.7 ± 1.3°, consistent with a previous study that reported 92 ± 2°, 39 suggesting that the ITO glass is slightly hydrophobic.…”
Section: Resultssupporting
confidence: 91%
“…38 The Q Y values of the graphene and graphene-CNC lms were 13.9 ± 2.7°and 64.0 ± 1.7°(n = 3, P = 0.0001), respectively, showing that graphene lms are more hydrophilic than graphene-CNC lms. The Q Y value of ITO was found to be 96.7 ± 1.3°, consistent with a previous study that reported 92 ± 2°, 39 suggesting that the ITO glass is slightly hydrophobic.…”
Section: Resultssupporting
confidence: 91%
“…Constructing a superhydrophobic surface can effectively alleviate the problem of its inability to resist corrosion and easy freezing during use [ 95 , 96 ]. It can also be given special functions such as self-cleaning, lubrication, and drag reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Coatings 2024, 14, 178 3 of 16 potentially interesting technical decision for microfluidics applications (as an alternative to ITO with UV treatment [45], patterned ITO [46], or ITO coated on a PET film [47]).…”
Section: Introductionmentioning
confidence: 99%